Mudanças organizacionais e diferenciação social: os trabalhadores da indústria do alumínio primário paraense - Barbosa, Attila Magno e Silva (2010)
This study intends to examine to what extent the organizational changes in industry of primary aluminum, in the city of Barcarena, Pará, lead to worker s adhesion and results differentiation in the social identities of direct and outsourced workers. Outsourced workers have a different status in the workplace, which excludes them from the benefits offered by the companies. As a result, society has to deal not only with the fragility of the wage relationship, but also with the collapse of the principles that regulate sociability among workers. The thesis is that the company organizational changes produce the adhesion of direct workers to the organizational ideas cause give them a feeling of colective belonging, even when we take into consideration the reduction of the workers that productive by lean production processes. Fifteen interviews were conducted with each group of workers; two union leaders were also interviewed. Furthermore, were examined the collective agreement between the direct workers and the company, and that company s yearly reports, since 2003.